Fostering Faith, Character, and Environmental Consciousness: The Holistic Approach of Christian Education in Early Childhood - Febri Manoppo (Montessori Jurnal Pendidikan Kristen Anak Usia Dini, 2023)
This study explores the role of environmentally friendly learning materials in Christian education for early childhood. Using a qualitative research approach with descriptive analysis, library research is employed as the primary data collection method. The study takes place at TK GMIM Anugerah Tingkulu in Manado City, involving a literature review on environmentally friendly learning materials and Christian Education concepts. Observations and interviews with kindergarten teachers are conducted for data analysis. The findings highlight the crucial role of Christian education in nurturing the faith, character, and spiritual growth of young children. It extends beyond teaching church-related knowledge and integrates principles aligned with Christian values. By incorporating environmentally friendly learning materials like recycled items and digital tools, TK GMIM Anugerah Tingkulu educators promote environmental consciousness and sustainability. Active parental involvement in creating recycled educational toys and adopting eco-friendly practices further enhances Christian character education. This integration of faith, knowledge, and environmental stewardship fosters a holistic learning experience, equipping children for a digital future while nurturing their spiritual and environmental well-being.